The effect of using a sports educational platform on the cognitive achievement of some team games for fifth grade middle school students - Salman, Waad; Al-Talib , Tariq (Journal of Physical Education, 2025)
The aim of the research is to influence, using an educational platform, the artistic achievement of some team games, and it adopted experimental users appropriate to the types of research. The research community was determined from the students of the fifth year of middle school at Baghdad Al-Karkh/Second College Secondary School, who numbered (66) students, and two students chose creativity in research from the community itself. Randomization was chosen by drawing a lottery, and (10) students who practiced games and (22) students sensing previous experiences were excluded, and the sample became composed of (34) students. The scale phrases were formulated in its initial form, which numbered (59) phrases, and they were presented to the scientific committee to approve the title of the research, as well as a group of experts, so its phrases were reduced to 40 phrases in its final form, after which the researchers designed the educational platform, then introduced the content for some team games skills, and it became accessible to every student who could The content of the lesson is reviewed through it, and then the scale was applied to the research sample.